PEMETAAN RAWAN BENCANA GEMPABUMI DI SEPANJANG SESAR LASEM BERDASARKAN NILAI PGA - Dini Vemirantih; Yohana Nooradika Maharani; Sorja Koesuma (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2025)
MAPPING OF EARTHQUAKE DISASTER PROTECTION Along the LASEM FAULT BASED ON PGA VALUES The region traversed by the Lasem Fault has a high potential for earthquake disasters, although no major recurring events have occurred to date. This condition makes the area particularly interesting for study, especially due to the limited amount of research and mitigation efforts based on quantitative data. This study aims to identify and map the seismic hazard levels around the Lasem Fault using the Deterministic Seismic Hazard Analysis (DSHA) approach, which has been widely implemented in earthquake risk assessments for its ability to provide deterministic estimates of Peak Ground Acceleration (PGA). PGA values are calculated at several points based on relevant earthquake source parameters and local site characteristics. The analysis results show a variation of PGA values, which are classified into several seismic hazard levels and then mapped to provide a visual representation of risk distribution. The results of the analysis are then mapped using QGIS and further processed with the InaSAFE plugin to identify public facilities located in vulnerable zones. This study recommends further investigation into the structural response of buildings to the predicted maximum ground shaking, as well as the integration of the findings into spatial planning policies, earthquake-resistant building design, and other mitigation efforts. The outcomes are expected to serve as a basis for informed decision-making in disaster risk reduction in areas affected by the Lasem Fault.